La afectividad familiar y su relación con la disciplina de las niñas y niños de quinto, sexto y séptimo grados del subnivel básica media de educación general básica, de la escuela de educación básica “Luis Antonio Erique Ortega”, barrio El Plateado, parroquia Sucre, de la ciudad de Loja. Año lectivo 2012-2013 - Quezada Paredes, Katy Silvana (2014)
The present investigation deals with the issue the relationship between family affection and discipline of children in fifth, sixth and seventh degrees of the average basic sublevel of basic General education, basic education school "Luis Antonio Erique Ortega", silver quarter, parroquia sucre from the city of Loja. 2012-2013 school year; It was raised as a general objective, to determine the relationship between family affection and discipline of children and girls. It is important to also point out that the following methodology was used: scientific method, descriptive method, method hypothetical - deductive, as well as the following techniques are used: direct observation, the structured interview and survey. The population was constituted by: a Director, 150 students, six teachers and 129 parents. Was raised as a hypothesis, if the family affection that receive children's fifth, sixth and seventh grade of the basic average sublevel of basic General education at the school of basic education "Luis Antonio Erique Ortega", in the 2012-2013 school year, significantly affects in your discipline and if inadequate discipline that children demonstrate is in relationship with the affection that parents and family members provide them. This research was carried out using methodological processes framed within the qualitative research, among the techniques and instruments used are: the interview custom, made to the principals and teachers of the above-mentioned educational institution and the application of questionnaires to parents and students; as a result of the research, giving confirmation of the assumptions made. Finally recommended to the Director and teachers of the school site, further enhance the formation of affective values in students who instruct at that institution, and the parents are encouraged to give greater attention to the emotional needs of their children to promote the timely dialogue and awareness of the human being's own attitudes to achieve emotionally stable individuals in society.